Proceedings of the 9th SIGdial Workshop on Discourse and Dialogue - SIGdial '08 2008
DOI: 10.3115/1622064.1622087
|View full text |Cite
|
Sign up to set email alerts
|

Training and evaluation of the HIS POMDP dialogue system in noise

Abstract: This paper investigates the claim that a dialogue manager modelled as a Partially Observable Markov Decision Process (POMDP) can achieve improved robustness to noise compared to conventional state-based dialogue managers. Using the Hidden Information State (HIS) POMDP dialogue manager as an exemplar, and an MDP-based dialogue manager as a baseline, evaluation results are presented for both simulated and real dialogues in a Tourist Information Domain. The results on the simulated data show that the inherent abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Although (28) can be used to optimise the policy parameters, the use of the "plain" gradient yields rather poor convergence properties since methods using this gradient often suffer from extremely flat plateaus in the expected reward function. In contrast, the natural gradient defined as…”
Section: Natural Actor Critic Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Although (28) can be used to optimise the policy parameters, the use of the "plain" gradient yields rather poor convergence properties since methods using this gradient often suffer from extremely flat plateaus in the expected reward function. In contrast, the natural gradient defined as…”
Section: Natural Actor Critic Algorithmmentioning
confidence: 99%
“…An appealing feature of these algorithms is that in practice the Fisher Information Matrix does not need to be explicitly computed. Inspecting (28), it can be observed that the expression…”
Section: Natural Actor Critic Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Training of the fixed back-off system starts in low noise and then incrementally increases it, as in [12]. Approximately 1, 000, 000 dialogues were used for training and the total number of grid points was 400.…”
Section: A Fixed Back-offmentioning
confidence: 99%
“…This gives rise to a rigid model of turntaking, which can be unnatural to users. There are many conditions under which users employ a more flexible turn-taking model, for example when they are under cognitive load and use more fillers, hesitations and barge-ins [1]. Furthermore, rigid turn-taking models often rely on a voice activity detection (VAD) component to decide whether the user is speaking or not, and this component can perform poorly, especially in noisy conditions, leading to confusion if the speech/non-speech classification is incorrect.…”
Section: Introductionmentioning
confidence: 99%